PERSONAL BRANDING DALAM KONTEKS PUBLIC RELATIONS: LITERATURE REVIEW DAN MODEL KONSEPTUAL - Muskita, Marleen; Pelamonia, Melinda (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research examines the evolution of personal branding in the context of Public Relations through a systematic literature review of 75 scientific articles published between 2020-2024. Using the PRISMA framework, this study identifies fundamental transformations in personal branding practices in the digital era. The analysis reveals a significant increase in digital platform adoption (85%) and the importance of an ethical framework comprising transparency, authenticity, and social impact. The study also highlights the crucial role of cultural intelligence in global personal branding effectiveness, with a 42% higher success rate among practitioners adopting culturally intelligent approaches. The integration of emerging technologies such as AI and analytics tools is shown to increase ROI by 35%. This research identifies contemporary challenges in personal branding, including privacy management, content saturation, and platform volatility. The main contribution of this study is the development of an integrated framework for personal branding that combines digital, ethical, and cultural aspects, along with practical recommendations for PR practitioners in optimizing personal brands in the digital era.